Delimitation of areas of environmental conflicts on the background of geological conditions, exemplified by Stary Sącz commune = Delimitacja obszarów konfliktów środowiskowych na tle uwarunkowań geologicznych na przykładzie gminy Stary Sącz - Gałaś, Slávka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Delimitation and characterization of areas of conflict are essential to assess suitability of land for different activities carried out in the field of rational land use. In the paper, delimitation of the conflict areas and conflicts categorization in terms of possibility of their overcoming, the scale of the range and the period of their occurrence exemplified by urban - rural commune Stary Sącz have been presented.
Keywords: delimitacja; uwarunkowania geologiczne; obszary konfliktów środowiskowych; konflikty środowiskowe; delimitation; geological conditions; areas of environmental conflicts; environmental conflicts